TiO2 modified nickel-based catalyst and method for preparing primary amine compound by using TiO2 modified nickel-based catalyst

By modifying the nickel-based catalyst by TiO2, using SiO2 support and Ni-TiO2 heterojunction, the problem of low hydrogen activation efficiency and insufficient selectivity of nickel-based catalysts at room temperature is solved, and the reduction of nitro compounds is achieved efficiently at room temperature is reduced. Reaction time and cost.

CN119215901APending Publication Date: 2024-12-31SOUTH CENTRAL UNIVERSITY FOR NATIONALITIES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411237903.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the prior art, the supported nickel-based catalyst does not have a high degree of activation to hydrogen at room temperature, resulting in a long reaction time and low chemical selectivity for nitro aromatic hydrocarbons containing reducing groups, which limits its nitro compounds. Application of hydrogenation to primary amines.

Method used

Using TiO2 modified nickel-based catalyst, SiO2 is used as a support to form a heterojunction between Ni and TiO2, improving the hydrogen activation efficiency, and using specific preparation methods and conditions, a high dispersion catalyst for nickel nanoparticles is prepared for room temperature. Catalyzing the reduction of nitro compounds.

Benefits of technology

It realizes efficient catalytic reduction of nitro compounds at room temperature, reduces reaction time and hydrogen pressure, improves the selectivity and cost-effectiveness of the catalyst, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005028281950000051
    Figure BDA0005028281950000051
  • Figure BDA0005028281950000071
    Figure BDA0005028281950000071
  • Figure BDA0005028281950000081
    Figure BDA0005028281950000081
Patent Text Reader

Abstract

The invention relates to the technical field of catalyst preparation, and particularly discloses a TiO2 modified nickel-based catalyst and a method for preparing a primary amine compound by using the TiO2 modified nickel-based catalyst. According to the TiO2 modified nickel-based catalyst disclosed by the invention, SiO2 is used as a carrier, and a heterojunction formed by Ni metal and TiO2 is used as an active component. The nickel-based catalyst disclosed by the invention can be obtained by loading non-noble metal ions through coprecipitation, then drying and finally calcining. The primary amine compound is prepared by using the TiO2 modified nickel-based catalyst, so that the requirement and the cost of the reaction on equipment are reduced, the operation safety is improved, and the reaction selectivity and the yield are higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and specifically relates to a TiO2-modified nickel-based catalyst and a method for preparing primary amine compounds using the same. Background Art

[0002] Amines are very important industrial intermediates and have been widely used as components of pharmaceuticals, agrochemicals, pigments, dyes and fine chemicals. Therefore, there has been increasing interest in the synthesis of amines in recent years. Nitro compounds are easily available, have good stability, and are starting materials for the synthesis of primary amines. Traditionally, primary amines are synthesized by reducing nitro compounds using stoichiometric reducing agents, such as sulfides, Fe and Zn. The use of stoichiometric reducing agents leads to high costs for the reduction of nitro compounds to primary amines. In addition, these methods also release a large amount of waste acid and residues. Therefore, catalytic hydrogenation of nitro compounds represents a green and sustainable method for the synthesis of primary amines.

[0003] Most of the methods for preparing nitro compounds (mainly nitrobenzene) disclosed in the prior art use precious metal catalysts and require high hydrogen pressure, which is not conducive to large-scale production. Currently, multiphase precious metal catalysts such as supported palladium, gold, and ruthenium have been widely used in the hydrogenation of nitroaromatics to synthesize functionalized anilines due to their excellent catalytic activity. However, the high cost of precious metal catalysts greatly limits their practical application. In addition, the chemical selective reduction of nitroaromatics containing reducible groups (C-Br, C=O, C=C, etc.) is also a huge challenge.

[0004] In recent years, many non-precious metal catalysts, mainly including Co, Ni and Fe, have been studied for hydrogenating nitro compounds to primary amines. Among various inexpensive catalysts, supported Ni catalysts have attracted great interest in catalytic hydrogenation reactions due to the excellent catalytic performance of Ni nanoparticles. Nickel nanoparticles supported by ordinary carriers can activate hydrogen at room temperature to catalyze hydrogenation of nitro compounds under the condition that the particle size is small enough. However, ordinary supported nickel-based catalysts still have the following two problems:

[0005] (1) The degree of activation of hydrogen at room temperature is not high, resulting in a very long reaction time;

[0006] (2) The chemical selectivity for nitroaromatic hydrocarbons containing reducing groups (C-Br, C=O, C=C, etc.) is not high. Summary of the invention

[0007] In order to solve the problems existing in the above-mentioned prior art, the invention aims to provide a TiO2-modified nickel-based catalyst and a method for preparing primary amine compounds using the same. The method for preparing the nickel-based catalyst of the present invention is simple and easy to operate, and can be used for selective catalytic reduction of nitro compounds to prepare primary amine compounds at room temperature.

[0008] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions:

[0009] In a first aspect, a TiO2-modified nickel-based catalyst is provided, wherein the TiO2-modified nickel-based catalyst uses SiO2 as a carrier and a heterojunction formed by Ni metal and TiO2 as an active component.

[0010] The nickel nanoparticles in the TiO2-modified nickel-based catalyst are highly dispersed, and the nickel nanoparticles D90 is less than 10 nm. Preferably, the average particle size is 6.61±1.72 nm.

[0011] The mass percentage content of Ni element in the TiO2-modified nickel-based catalyst is 9.7%-10.1%, and the mass percentage content of Ti element is 0.6%-3%; preferably, the mass percentage content of Ni element in the TiO2-modified nickel-based catalyst is 9.7%-10.0%, and the mass percentage content of Ti element is 1.6%-3%; more preferably, the mass percentage content of Ni element in the TiO2-modified nickel-based catalyst is 9.9%-10.0%, and the mass percentage content of Ti element is 2.5%-2.6%.

[0012] In a second aspect, a method for preparing a TiO2-modified nickel-based catalyst comprises the following steps:

[0013] (1) Add nano-SiO2, Ni(NO3)2·6H2O and urea to deionized water, heat it to 90-100°C while stirring, then drop concentrated hydrochloric acid and TiCl4 in turn, keep the temperature and stir for 18-24 hours to obtain a mixed solution;

[0014] (2) cooling the mixed solution to room temperature, filtering with suction, washing the filter cake with water until the pH is neutral, drying, and grinding to obtain a solid powder;

[0015] (3) In a hydrogen atmosphere, the solid powder is heated to 350-550° C., kept at this temperature for calcination for 2-4 hours, taken out, and ground to obtain a TiO2-modified nickel-based catalyst.

[0016] Furthermore, in step (1), the particle size of nano-SiO2 is 15-25nm.

[0017] Furthermore, in step (1), the dosage ratio of nano-SiO2, Ni(NO3)2·6H2O and urea is 10mmol:1mmol:1g, and the dosage ratio of nano-SiO2 and TiCl4 is 60mmol:(0.05-0.35)mL, preferably 60mmol:(0.15-0.35)mL, more preferably 60mmol:(0.20-0.30)mL, and most preferably 60mmol:0.25mL.

[0018] Furthermore, in step (1), the usage ratio of nano-SiO2 to deionized water is 6mmol:(8-10)mL.

[0019] Furthermore, in step (1), the concentration of concentrated hydrochloric acid is 36wt%-38wt%, and the volume ratio of concentrated hydrochloric acid to TiCl4 is 1:1.

[0020] Furthermore, in step (2), the drying conditions are: drying at 60-90°C for 12-24h; preferably, drying at 70°C for 12h.

[0021] Furthermore, in step (3), the solid powder is heated to 400-500° C. and calcined at this temperature for 3-4 hours; preferably, the solid powder is heated to 450° C. and calcined at this temperature for 4 hours.

[0022] Furthermore, in step (3), the solid powder is heated at a heating rate of 2-4°C / min.

[0023] In a third aspect, a method for preparing a primary amine compound using the above-mentioned TiO2-modified nickel-based catalyst or the TiO2-modified nickel-based catalyst prepared by the above-mentioned method comprises the following steps:

[0024] A TiO2-modified nickel-based catalyst, an organic solvent and a nitro organic compound are added to a high-pressure reactor, which is sealed and replaced with H2 to displace the air in the reactor. The autoclave is pressurized and sealed with 5-20 bar H2, and then reacted at 20-30° C. with constant stirring to obtain an amine compound in which only the nitro group is reduced and reduced to an amino group.

[0025] Furthermore, the solvent is one of toluene, dichloromethane, tetrahydrofuran and ethyl acetate, preferably toluene.

[0026] Furthermore, the usage ratio of the TiO2-modified nickel-based catalyst, the organic solvent and the nitro-organic compound is (5-30) mg:10 mL:0.5 mmol, preferably 20 mg:10 mL:0.5 mmol.

[0027] Further, the autoclave is pressurized and sealed with 10-15 bar H2, and then the reaction is carried out at 20-30°C with constant stirring, preferably for more than 2 hours, more preferably for more than 4 hours, more preferably for more than 6 hours, and more preferably for more than 8 hours.

[0028] Further, the nitro organic compound is nitrobenzene or substituted nitrobenzene, wherein the substituted nitrobenzene is monosubstituted, the substitution position is ortho, meta or para, preferably para, and the substituent is CH2=CH-, -CH3, -OCH3, -CH2OH, -F, -Cl, -CF3, -CCl3, -CN, -COCH3, -CHO; substituted nitrobenzene is, for example:

[0029] Any one of p-nitrostyrene, nitrobenzene, o-nitrotoluene, m-nitrotoluene, p-nitrotoluene, p-methoxynitrobenzene, p-nitrobenzyl alcohol, p-fluoronitrobenzene, p-chloronitrobenzene, p-trifluoromethylnitrobenzene, p-nitrobenzonitrile, p-nitroacetophenone and p-nitrobenzaldehyde.

[0030] Furthermore, the nitro organic compound is a non-aromatic nitro organic compound, such as nitrocyclohexane and 3-nitropropane.

[0031] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0032] 1. The preparation method of the TiO2-modified nickel-based catalyst of the present invention is very simple, and nano-SiO2 is used as a carrier, and non-precious metal ions are loaded by co-precipitation of Ni(NO3)2·6H2O and TiCl4 under the action of urea, and then dried, and finally calcined to obtain the catalyst. The co-precipitation of Ni and TiO2 has a stronger interaction, wherein the Ni-TiO2 interface forms a heterojunction, and the activation efficiency of hydrogen is higher, and the oxygen vacancies on the TiO2 surface and the smaller nickel nanoparticles can reduce the lying adsorption of the substrate and improve the substrate selectivity.

[0033] 2. The method of the present invention uses the above-prepared TiO2-modified nickel-based catalyst to catalyze the reduction of nitro organic matter to prepare primary amines. Compared with the existing method, the reaction temperature can reach room temperature and low hydrogen pressure, which reduces the equipment requirements and cost of the reaction and improves the safety of operation.

[0034] 3. The present invention utilizes a relatively low-cost SiO2-loaded TiO2-modified nickel-based catalyst to prepare primary amine compounds. Compared with the existing method for preparing primary amine compounds, it not only has low cost but also has high reaction selectivity and high yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Transmission electron microscope image and particle size distribution diagram of the nickel-based catalyst prepared in Example 1.

[0036] Figure 2 This is the X-ray diffraction pattern (XRD pattern) of the nickel-based catalyst prepared in Example 1.

[0037] Figure 3 This is the X-ray photoelectron spectrum (XPS spectrum) of the nickel-based catalyst prepared in Example 1.

[0038] Figure 4 This is the electron paramagnetic resonance spectrum (EPR spectrum) of the nickel-based catalyst prepared in Example 1.

[0039] Figure 5 Transmission electron microscope image and particle size distribution diagram of the nickel-based catalyst prepared in Example 2.

[0040] Figure 6 This is the X-ray diffraction pattern (XRD pattern) of the nickel-based catalyst prepared in Example 2. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and drawings, but the following embodiments are not intended to limit the scope of protection requested by the claims of the present invention.

[0042] The nickel nitrate hexahydrate used in the following examples was purchased from Aladdin with batch number N140967; the urea used was purchased from Aladdin with batch number H2314332; the hydrochloric acid used was purchased from Shanghai Test Chemical Reagent Co., Ltd. with batch number 20240108; the silicon dioxide used was purchased from Xianfeng Nanomaterials Co., Ltd. with a particle size of 25 nm and batch number y2734189; the titanium tetrachloride used was purchased from Aladdin with batch number A2125108; the titanium dioxide used was purchased from Aladdin with a particle size of 25 nm and batch number A2107130.

[0043] Example 1

[0044] A TiO2-modified nickel-based catalyst is prepared by the following method:

[0045] 1) Add 3.6 g (60 mmol) SiO2, 1.745 g (6 mmol) Ni(NO3)2·6H2O, and 6 g (0.1 mol) urea to 100 mL deionized water, then transfer to an oil bath, keep stirring, raise the temperature to 95°C, add 0.25 mL 36.5 wt% HCl and 0.25 mL (2.27 mmol) TiCl4 dropwise in sequence, and stir vigorously at 95°C for 24 h.

[0046] 2) After the mixed solution obtained in step 1) is cooled to room temperature, it is filtered and washed with deionized water until the pH is neutral. The obtained solid sample is dried at 70° C. for 12 h, cooled, and ground to obtain a solid powder.

[0047] 3) In a H2 atmosphere, the solid powder obtained in step 2) was heated from room temperature to 450°C at a heating rate of 4°C / min, kept warm for 4 hours, cooled to room temperature, taken out, and ground into powder to obtain the TiO2-modified nickel-based catalyst, wherein the molar ratio of Ti:Ni in the raw material was 0.380, and was named NiTi 0.380 @SiO2.

[0048] Only the amount of 36.5wt% HCl and TiCl4 in step 1) is adjusted, and the volume ratio of the two is 1:1. The addition of 36.5wt% HCl is to slow down the hydrolysis rate of TiCl4, and its volume changes with the volume of TiCl4. The amount of TiCl4 is 0.05mL TiCl4, 0.15mL TiCl4, and 0.35mL TiCl4 respectively. The other steps remain unchanged, and finally NiTi is obtained. 0.076 @SiO2,NiTi 0.228 @SiO2,NiTi 0.532 @SiO2 catalyst.

[0049] The contents of Ni and Ti in the catalyst were determined by inductively coupled plasma optical emission spectroscopy (ICP-OES). The results are shown in Table 1 below:

[0050] Table 1

[0051]

[0052] Example 2

[0053] A SiO2-supported nickel-based catalyst is prepared by the following method:

[0054] 1) Add 3.6 g (60 mmol) SiO2 and 1.745 g (6 mmol) Ni(NO3)2·6H2O to 100 mL deionized water and stir at room temperature for 4 h.

[0055] 2) The mixed solution obtained in step 1) was filtered and washed with deionized water until the pH was neutral. The obtained solid sample was dried at 70° C. for 12 h, cooled, and ground to obtain a solid powder.

[0056] 3) Under H2 atmosphere, the solid powder obtained in step 2) was heated from room temperature to 450°C at a heating rate of 4°C / min, kept warm and calcined for 4 hours, and after cooling to room temperature, taken out and ground into powder to obtain the commercial SiO2-supported nickel-based catalyst, named NiTi0@SiO2.

[0057] The Ni content in the catalyst was determined by inductively coupled plasma optical emission spectroscopy (ICP-OES) and was 10.13 wt.%.

[0058] Example 3 A TiO2-supported nickel-based catalyst was prepared by the following method:

[0059] 1) Add 4.8 g (60 mmol) TiO2 and 1.745 (6 mmol) g Ni(NO3)2·6H2O to 100 mL deionized water and stir at room temperature for 4 h.

[0060] 2) The mixed solution obtained in step 1) was filtered and washed with deionized water until the pH was neutral. The obtained solid sample was dried at 70° C. for 12 h, cooled, and ground to obtain a solid powder.

[0061] 3) Under H2 atmosphere, the solid powder obtained in step 2) was heated from room temperature to 450°C at a heating rate of 4°C / min, kept warm and calcined for 4 hours, and after cooling to room temperature, taken out and ground into powder to obtain the TiO2-supported nickel-based catalyst, named NiTi0@TiO2.

[0062] Characterization results

[0063] 1. The SiO2-loaded TiO2-modified nickel-based catalyst (NiTi 0.380 @SiO2) characterization:

[0064] 1. The transmission electron microscopy images obtained are as follows: Figure 1 As shown in (a) and (b), it can be clearly seen from the figure that nickel nanoparticles are uniformly loaded on the SiO2 surface, and the particle size distribution is as follows Figure 1 As shown in (c), the average particle size is 6.61±1.72nm. In addition, obvious TiO2(101) lattice can be seen around the nickel nanoparticles, indicating that the TiO2 and Ni 2+ At the same time, Ni metal and TiO2 form an active species heterojunction Ni-TiO 2-x (x represents the number of electrons transferred from TiO2 to nickel nanoparticles).

[0065] 2. The obtained X-ray diffraction pattern is as follows Figure 2 As shown, from Figure 2 It can be seen that the three peaks at 2θ=44.4°, 51.9° and 76.5° are all characteristic peaks of nickel nanoparticles, indicating the presence of nickel nanoparticles; in addition, the diffraction peak of TiO2 can also be seen in the figure, indicating the presence of TiO2.

[0066] 3. The obtained X-ray photoelectron spectrum is as follows: Figure 3 As shown. Figure 3 In (a), it can be seen that the catalyst mainly contains Si, O, Ti and Ni elements. Figure 3As shown in (b), the peaks at 852.53eV, 856.81eV, 862.84eV, 874.71eV, and 880.50eV are respectively attributed to Ni 0 2p 3 / 2 Peak, Ni 2+ 2p 3 / 2 Peak, Ni 2+ 2p 3 / 2 Satellite peak, Ni 2+ 2p 1 / 2 Peak, Ni 2+ 2p 1 / 2 Satellite peak. It can be seen from the figure that Ni 0 The peak shifts toward the low binding energy direction with the increase of TiO2 amount, indicating that the electron transfer from TiO2 to nickel nanoparticles occurs due to the strong metal-support interaction between nickel nanoparticles and TiO2. Figure 3 As shown in (c), the 2p 3 / 2 The peaks can be divided into Ti 3+ and Ti 4+ The peak further indicates that electrons are transferred from TiO2 to nickel nanoparticles. However, as the amount of TiO2 increases, TiO2 will also cover nickel nanoparticles, resulting in reduced exposure of active sites, thereby reducing the reaction rate.

[0067] 4. The obtained electron paramagnetic resonance spectrum is as follows Figure 4 As shown, g = 2.003 is the spin resonance signal of the free electrons of the oxygen vacancies in the catalyst. The results show that with the increase of the amount of TiO2, the concentration of oxygen vacancies in the catalyst increases, which means that the greater the concentration of oxygen vacancies in the catalyst, the better the selectivity for amine compounds.

[0068] 2. Characterization of the SiO2-supported nickel-based catalyst prepared in Example 2:

[0069] 1. The transmission electron microscopy images obtained are as follows: Figure 5 As shown in (a) and (b), it can be seen from the figure that there are obvious nickel nanoparticles on the surface of the SiO2 carrier. The nickel nanoparticles are seriously accumulated and their particle size distribution is as follows Figure 5 As shown in (c), the average particle size is 14.37±6.93 nm.

[0070] 2. The obtained X-ray diffraction pattern is as follows Figure 6 As shown in the figure, the three peaks at 2θ=44.4°, 51.9° and 76.5° are all characteristic peaks of nickel nanoparticles. The SiO2-loaded nickel-based catalyst prepared by the impregnation method has obvious diffraction peaks of nickel species, indicating that the nickel nanoparticles in the nickel-based catalyst prepared by this method are unevenly dispersed and have a larger particle size, which is consistent with the TEM spectrum results.

[0071] Embodiment 4-9

[0072] The method for preparing primary amine compounds using the nickel-based catalyst prepared in Example 1-3 comprises the following steps:

[0073] 10 mL of toluene, 0.5 mmol of p-nitrostyrene and 20 mg of catalyst were added to the autoclave, the autoclave was sealed, the air was replaced with hydrogen for 5 times, 10 bar of hydrogen was introduced and sealed, and the autoclave was heated to 30° C. under a hydrogen atmosphere while stirring, and the temperature was kept warm and stirred for 4 hours to obtain a reduction product. After the reaction was completed, the spent catalyst was collected by centrifugation, and the product was identified by gas chromatography-mass spectrometry (GC-ms) with ethylbenzene as the internal standard, and the product was quantitatively analyzed by GC (Shimadzu, GC-2010 Plus), the same below.

[0074] The results of selective hydrogenation of p-nitrostyrene by different catalysts are shown in Table 2. As shown in Table 2:

[0075] The catalyst NiTi0@SiO2 prepared in Example 2 showed catalytic activity in the catalytic conversion of p-nitrostyrene, but the selectivity for the target product p-aminostyrene was 55.1%; the catalyst NiTi0@TiO2 prepared in Example 3 showed high catalytic activity in the catalytic conversion of p-nitrostyrene, but the selectivity for the target product p-aminostyrene was only 26.2%. The catalysts NiTi0@SiO2 and NiTi0@TiO2 could not selectively reduce the nitro group in the presence of other reducible groups such as vinyl.

[0076] The catalyst NiTi@SiO2 prepared in Example 1 shows catalytic activity for p-nitrostyrene, can inhibit the hydrogenation of vinyl in p-nitrostyrene, and has low selectivity for the product p-ethylaniline, that is, it can selectively reduce the nitro group. 0.380 @SiO2 catalyst has the best effect, with a conversion rate of 62.2% for p-nitrostyrene and a selectivity of 100% for the product p-aminostyrene.

[0077] Table 2

[0078]

[0079] In addition, based on Example 1, the present invention continues to adjust the dosage ratio of nano-SiO2 and TiCl4 to 60mmol: (0.20-0.30)mL, and the prepared catalyst is subjected to catalytic reaction according to the method and conditions of this example, and the conversion rate of nitrostyrene is above 60%, and the selectivity of aminostyrene is above 95%.

[0080] Examples 10-17

[0081] In order to optimize the NiTi prepared in Example 1 0.380 @The reaction conditions for the selective catalytic hydrogenation of p-nitrostyrene using SiO2 catalyst are the same as those in Example 8, except that only the type of reaction solvent is changed. p-Aminostyrene and nitrosobenzene are obtained in the same manner.

[0082] The effects of different solvents on the reduction of p-nitrostyrene are shown in Table 3. It can be seen from Table 3 that when toluene, dichloromethane, tetrahydrofuran and ethyl acetate are used as solvents, the selectivity of the catalyst for p-aminostyrene is as high as 100%, among which, when toluene is used as solvent, the conversion rate of p-nitrostyrene is the highest, which is 62.2%. Therefore, toluene is the best solvent for this reaction system.

[0083] Table 3 Effect of different solvents on the reduction of p-nitrostyrene

[0084]

[0085] Examples 19-22

[0086] In order to optimize the NiTi prepared in Example 1 0.380 @The reaction conditions for the selective catalytic hydrogenation of p-nitrostyrene using SiO2 catalyst are the same as the operating method and steps of Example 8, except that only the H2 pressure is changed, and p-aminostyrene and nitrosobenzene are also obtained.

[0087] The effects of different H2 pressures on the reduction of p-nitrostyrene are shown in Table 4. It can be seen from Table 4 that the H2 pressure is positively correlated with the catalytic efficiency. When the H2 pressure is 15 bar, the conversion rate is the highest, reaching 74%.

[0088] Table 4 Effect of different H2 pressures on the reduction of p-nitrostyrene

[0089]

[0090]

[0091] Examples 23-27

[0092] In order to optimize the NiTi prepared in Example 1 0.380 @The reaction conditions for the selective catalytic hydrogenation of p-nitrostyrene using SiO2 catalyst are the same as the operating method and steps of Example 8, only the reaction time is changed, and p-aminostyrene and nitrosobenzene are also obtained.

[0093] The effects of different reaction times on the reduction of p-nitrostyrene are shown in Table 5. It can be seen from Table 5 that the conversion rate gradually increases to 100% in the first 8 hours of the reaction.

[0094] Table 5 Effect of different reaction times on the reduction of p-nitrostyrene

[0095]

[0096] Embodiment 28-41

[0097] In order to optimize the NiTi prepared in Example 1 0.380 @The applicable substrate range of SiO2 catalyst is the same as that of Example 8. The conversion rate and yield of the obtained primary amine compound (product) are different by changing the type of nitro compound and the reaction time. 0.380 The reaction activity of @SiO2 catalyst towards different substrates is shown in Table 6.

[0098] Table 6 NiTi 0.380 Reactivity of @SiO2 catalysts towards different substrates

[0099]

[0100]

[0101] Examples 42-47

[0102] In order to study the NiTi prepared in Example 1 0.380 @ Catalytic stability of SiO2 catalyst, according to the operation method and steps of Example 8, under the following reaction conditions: p-nitrostyrene (0.5 mmol), catalyst (20 mg), toluene (10 mL), H2 (10 bar) , The reaction was carried out at 30°C for 8h. After the reaction, the catalyst was collected by centrifugation and washed with distilled water, and then the washed catalyst was dried at 40°C in vacuum for 12 hours and used for the next cycle. The results of the cycle test are shown in Table 7. As shown in Table 7, during the 6 cycles studied, the conversion of p-nitrostyrene in 6 runs was almost quantitative, and the selectivity of p-aminostyrene remained stable at more than 99.1%. All results show that the catalyst has good repeatability and stability.

[0103] Table 7 Cyclic test

[0104]

Claims

1. A TiO2-modified nickel-based catalyst, characterized in that: The TiO2-modified nickel-based catalyst uses SiO2 as a carrier and a heterojunction formed by Ni metal and TiO2 as an active component.

2. The TiO2-modified nickel-based catalyst according to claim 1, characterized in that The nickel nanoparticles in the TiO2-modified nickel-based catalyst are highly dispersed, and the nickel nanoparticles have a D90 of less than 10 nm. Preferably, the average particle size is 6.61±1.72 nm; and / or The mass percentage content of Ni element in the TiO2-modified nickel-based catalyst is 9.7%-10.1%, and the mass percentage content of Ti element is 0.6%-3%; preferably, the mass percentage content of Ni element in the TiO2-modified nickel-based catalyst is 9.7%-10.0%, and the mass percentage content of Ti element is 1.6%-3%; more preferably, the mass percentage content of Ni element in the TiO2-modified nickel-based catalyst is 9.9%-10.0%, and the mass percentage content of Ti element is 2.5%-2.6%.

3. A method for preparing a TiO2-modified nickel-based catalyst according to any one of claims 1 to 2, characterized in that: The steps include: (1) Add nano-SiO2, Ni(NO3)2·6H2O and urea to deionized water, heat it to 90-100°C while stirring, then drop concentrated hydrochloric acid and TiCl4 in turn, keep the temperature and stir for 18-24 hours to obtain a mixed solution; (2) cooling the mixed solution to room temperature, filtering with suction, washing the filter cake with water until the pH is neutral, drying, and grinding to obtain a solid powder; (3) In a hydrogen atmosphere, the solid powder is heated to 350-550° C., kept at this temperature for calcination for 2-4 hours, taken out, and ground to obtain a TiO2-modified nickel-based catalyst.

4. The preparation method according to claim 3, characterized in that: In step (1), the particle size of nano-SiO2 is 15-25nm; the dosage ratio of nano-SiO2, Ni(NO3)2·6H2O and urea is 10mmol:1mmol:1g, and the dosage ratio of nano-SiO2 and TiCl4 is 60mmol:(0.05-0.35)mL, preferably 60mmol:(0.15-0.35)mL, more preferably 60mmol:(0.20-0.30)mL, and most preferably 60mmol:0.25mL.

5. The preparation method according to claim 3, characterized in that: In step (1), the concentration of concentrated hydrochloric acid is 36wt%-38wt%, and the volume ratio of concentrated hydrochloric acid to TiCl4 is 1:1; and / or In step (1), the usage ratio of nano-SiO2 to deionized water is 6mmol:(8-10)mL.

6. The preparation method according to claim 3, characterized in that: In step (2), the drying conditions are: drying at 60-90°C for 12-24h; preferably, drying at 70°C for 12h.

7. The preparation method according to claim 3, characterized in that: In step (3), the solid powder is heated to 400-500° C. and calcined at this temperature for 3-4 hours; preferably, the solid powder is heated to 450° C. and calcined at this temperature for 4 hours.

8. A method for preparing primary amine compounds using a TiO2-modified nickel-based catalyst as described in any one of claims 1-2 or a TiO2-modified nickel-based catalyst prepared by the method as described in any one of claims 3-7, characterized in that: The steps include: A TiO2-modified nickel-based catalyst, an organic solvent and a nitro-organic compound are added to a high-pressure reactor, the air in the reactor is replaced with H2 after sealing, the high-pressure reactor is pressurized and sealed with 5-20 bar H2, and then reacted at 20-30° C. with constant stirring to obtain an amine compound in which only the nitro group is reduced and reduced to an amino group; The solvent is one of toluene, dichloromethane, tetrahydrofuran and ethyl acetate.

9. The method according to claim 8, characterized in that The amount ratio of the TiO2-modified nickel-based catalyst, the organic solvent and the nitro-organic compound is (5-30) mg:10 mL:0.5 mmol, preferably 20 mg:10 mL:0.5 mmol; Preferably, the autoclave is pressurized and sealed with 10-15 bar H2, and then the reaction is carried out at 20-30°C with constant stirring, preferably for more than 2 hours, more preferably for more than 4 hours, more preferably for more than 6 hours, and more preferably for more than 8 hours.

10. The method according to claim 8, characterized in that The nitro organic matter is nitrobenzene, substituted nitrobenzene or non-aromatic nitro organic matter, in which the substituted nitrobenzene is monosubstituted, the substitution position is ortho, meta or para, and the substituent is CH2=CH-, -CH3, -OCH3, -CH2OH, -F, -Cl, -CF3, -CCl3, -CN, -COCH3, -CHO; preferably, the nitro organic matter is any one of p-nitrostyrene, nitrobenzene, o-nitrotoluene, m-nitrotoluene, p-nitrotoluene, p-methoxynitrobenzene, p-nitrobenzene alcohol, p-fluoronitrobenzene, p-chloronitrobenzene, p-trifluoromethylnitrobenzene, p-nitrobenzonitrile, p-nitroacetophenone, p-nitrobenzaldehyde, nitrocyclohexane and 3-nitropropane.